Is tree ring chronology of blue pine (Pinus wallichiana A. B. Jackson) prospective for summer drought reconstruction in the Western Himalaya?. (15th May 2022) - Dhyani, Rupesh; Bhattacharyya, Amalava; Singh Rawal, Ranbeer; Joshi, Rajesh; Shekhar, Mayank; Singh Ranhotra, Parminder
Graphical abstract: Highlights: Tree ring chronology of blue pine is potential for long term SPEI (drought index) reconstruction. Provides a reliable drought records (322-year's) during monsoon season of the western Himalaya. The spectral peaks (2–4 years) indicate drought fluctuations are linked mostly to ENSO events. The reconstructed monsoon SPEI showed notable drying towards 1990 to 2017AD. Abstract: A long record of drought beyond observable data is scarce in the Himalayan region, making it difficult to understand the region's long-term variability. Here we reconstructed the Standardized Precipitation Evapotranspiration Index (SPEI) a drought index using the tree-ring chronology of blue pine ( Pinus wallichiana ), to retrieve the past drought variations. The chronology is prepared from tree ring width series of well replicated samples of blue pine covering time span of 1660–2017 CE, from Darma Valley, Indian Western Himalaya. We observed that the combined expression of precipitation and temperature, conveyed as SPEI, is more effective in limiting tree growth during the monsoon season than either precipitation or temperature alone. The SPEI of June-September (monsoon season) exhibited a significant strong positive correlation (r = + 0.69,  p < 0.001) with the tree ring chronology. Based on this relationship, we reconstructed monsoon SPEI covering 1696–2017 CE. The variance explained for the calibration period 47% of the actual SPEI variance of 1903–2017 CE. The extended SPEI time series indicates several high and low intensity droughts, which are consistent with the historical drought records of the Himalayan region. Furthermore, analyses of the spatial correlations reveal that the variation in the reconstructed monsoon SPEI is strongly associated with the regional summer drought variability in the Himalayan region. We recorded a strong teleconnection of SPEI data and sea surface temperature changes in the Indian and Pacific Oceans, indicating that Indian summer monsoon variability is prevalent for this region's summer monsoon SPEI. Furthermore, in the spectral analysis peaks between 2.0 and 4.0 years indicates that the summer drought fluctuation is linked to El Niño-Southern Oscillation (ENSO).